PENGEMBANGAN DIGITAL MARKETING WISATA BOYOLAYAR-KEDUNG OMBO PADA MASA PANDEMI COVID-19 - Nafiah Ariyani (Penerbit Widina, Widina Media Utama, 2022)
Boyolayar Tourism is one of the tourist destinations in the Kedung Ombo reservoir area, which was forced to close due to the Covid 19 pandemic. The implementation of PPKM has resulted in no visitors to this tourist destination, resulting in abandoned locations and tourist rides and declining popularity. Therefore, intensive promotion is needed to help restore the popularity of Boyolayar tourism and encourage tourists to come. This PKM activity aims to help tourist destination managers re-strengthen Boyolayar's tourist attractions through the development of digital promotional media. Activities carried out to include 1. counseling on digital marketing for tourism; 2. training on account creation and social media content management, and 3. development of the Boyolayar tourist village website. The methods used are lecture, discussion, and practice. The activity was followed by the manager of the Boyolayar tourist village and carried out in one of the Boyolayar tourist spots for six days. The activity has resulted in 1. understanding of the management of the Boyolayar tourism village about the importance of digital-based marketing and promotion; 2. the formation of interesting and informative Facebook and Instagram social media accounts; and 3. the establishment of the Boyolayar website.